2011
DOI: 10.3114/sim.2011.70.02
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of Penicillium section Citrina

Abstract: Species of Penicillium section Citrina have a worldwide distribution and occur commonly in soils. The section is here delimited using a combination of phenotypic characters and sequences of the nuclear ribosomal RNA gene operon, including the internal transcribed spacer regions ITS1 and ITS2, the 5.8S nrDNA (ITS) and partial RPB2 sequences. Species assigned to section Citrina share the production of symmetrically biverticillate conidiophores, flask shaped phialides (7.0–9.0 μm long) and relatively small conidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(121 citation statements)
references
References 46 publications
9
110
0
2
Order By: Relevance
“…Studies on the natural Cannabis microbiome have identified several species of culturable endophytic fungi, including Penicillium citrinum, Penicillium copticola (a member of the citrinum section 9 ) and several Aspergillus species 10, 11 . Similar studies looking at culturable bacterial endophytes identified nearly a dozen isolates from the Bacillus clade and two mycobacteria 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the natural Cannabis microbiome have identified several species of culturable endophytic fungi, including Penicillium citrinum, Penicillium copticola (a member of the citrinum section 9 ) and several Aspergillus species 10, 11 . Similar studies looking at culturable bacterial endophytes identified nearly a dozen isolates from the Bacillus clade and two mycobacteria 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the ITS region was accepted as the prime fungal barcode (25). In contrast to other related genera, such as Aspergillus and Penicillium (26)(27)(28), all Rasamsonia species can be identified with ITS sequences. It has been suggested that clinical laboratories refer to a complex rather than a species in their report when no molecular-based identification is undertaken (29,30).…”
Section: Figmentioning
confidence: 99%
“…For example, as some secondary metabolites were formed by P. steckii on a rice medium, quite different metabolites were produced by the same strain on white beans. Some of the same compounds were found by Malmstrøm et al [129] and Houbraken et al [130] on the media CYA and YES, but not all of them. Similarly, P. citrinum produced nine secondary metabolites on white beans and six other secondary metabolites on rice [131].…”
Section: Secondary Metabolite Profiles and (One Strains Many Compoundmentioning
confidence: 51%
“…Similarly, P. citrinum produced nine secondary metabolites on white beans and six other secondary metabolites on rice [131]. Several of those were also produced on CYA and YES agar [130], but on white beans P. citrinum produced alternariol, never reported before from that species. A combination of CYA, YES, rice, and white beans seems to allow expression of many secondary metabolites in many species of fungi, but special ecological groups of fungi may need modified media to be able to produce and accumulate their secondary metabolites.…”
Section: Secondary Metabolite Profiles and (One Strains Many Compoundmentioning
confidence: 92%